REFORMASI PEMIKIRAN HUKUM ISLAM - Sulaeman, Budiman (DIKTUM: Jurnal Syariah dan Hukum, 2013)
Muslim community is very much dependant upon classic fiqh books, so that they are fiqh-minded. They assume that the product of fiqh in classic books is identical with Divine law. It is this phenomenon of sacralization that that makes Islamic law stagnant in Muslim counties.This problem must be overcome by inserting the understanding that Islamic law in its normative level should be present as a solution to actual social problems. In this regard, the methodology of classic Islamic legal theory (ushÃ»l fiqh) and fiqh should be considered as a historical response towards their contemporary situations.